2021
DOI: 10.1002/pro.4110
|View full text |Cite
|
Sign up to set email alerts
|

Low amounts of heavy water increase the phase separation propensity of a fragment of the androgen receptor activation domain

Abstract: The phase equilibria of intrinsically disordered proteins are exquisitely sensitive to changes in solution conditions and this can be used to investigate the driving forces of phase separation in vitro as well as the biological roles of phase transitions in live cells. Here we investigate how using D2O as co‐solvent in an aqueous buffer changes the phase equilibrium of a fragment of the activation domain of the androgen receptor, a transcription factor that plays a role in the development of the male phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…Within this context, recent discoveries regarding phase separation of AR are of high interest. It has been demonstrated that the intrinsically disordered N-terminal domain of AR forms liquid-like droplets in vitro at ∼100 μM ( 17 ), and the isolated Tau 5 region within this NTD at ∼500 μM ( 18 ). Moreover, the isolated DBD was shown to undergo phase separation in presence of RNA (poly U) ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Within this context, recent discoveries regarding phase separation of AR are of high interest. It has been demonstrated that the intrinsically disordered N-terminal domain of AR forms liquid-like droplets in vitro at ∼100 μM ( 17 ), and the isolated Tau 5 region within this NTD at ∼500 μM ( 18 ). Moreover, the isolated DBD was shown to undergo phase separation in presence of RNA (poly U) ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some important steps have been taken including insights from single‐molecule fluorescence resonance energy transfer (smFRET), electron paramagnetic resonance (EPR), and nuclear magnetic resonance (NMR) 13 . However, none have been applied successfully to resolve the structure of the full‐length AR‐NTD due to technical difficulties 14–16 …”
Section: Introductionmentioning
confidence: 99%
“…13 However, none have been applied successfully to resolve the structure of the fulllength AR-NTD due to technical difficulties. [14][15][16] The intrinsic disorder poses a challenge not only for experimental analysis of the conformation but also for computational modeling of the chain due to the size of the conformation space and lack of stable folds. For example, the state-of-the art artificial intelligence-based prediction approaches fail to identify the conformation of AR-NTD.…”
Section: Introductionmentioning
confidence: 99%
“…Another fluorinated molecule (TFT) in a coaxial insert acts as an external reference 39 , and enables observation of magnetic field inhomogeneity emerging as a result of macroscopic layer separation, without the complication of the reference solution itself participating in LLPS. The coaxial insert is also crucial for housing deuterated solvent for field-frequency lock required by the NMR spectrometer, thereby avoiding the addition of 2 H 2 O directly to the protein solution, which is known to alter the LLPS propensity of proteins 33 , 40 , 41 . Despite the presence of two distinct phases emerging during the initial microscopic phase separation, magnetic field homogeneity, as judged by TFT signal lineshape, is initially remarkably unperturbed.…”
Section: Discussionmentioning
confidence: 99%